The people's hospital : hope and peril in American medicine - Nuila, Ricardo, 1978- (Scribner, 2023)
"Where does one go without health insurance, when turned away by hospitals, clinics, and doctors? In The People's Hospital, physician Ricardo Nuila's stunning debut, we follow the lives of five uninsured Houstonians as their struggle for survival leads them to a hospital where insurance comes second to genuine care. Each patient eventually lands at Ben Taub, the county hospital where Dr. Nuila has worked for over a decade. Nuila delves with empathy into the experiences of his patients, braiding their dramas into a singular narrative that contradicts the established idea that the only way to receive good healthcare is with good insurance. As readers follow the movingly rendered twists and turns in each patient's story, it's impossible to deny that our system is broken--and that Ben Taub's innovative model, which emphasizes people over payments, could help light the path forward."--